SOME EVERYDAY RITUALS IN MANAGEMENT CONTROL* - Golding, David (Journal of Management Studies, 1991)
ABSTRACTThis article examines the way in which observed rituals in management activity appear to contribute to the accomplishment of management control. It argues that any examination of organizational activity involving a dimension so ethereal as ritual is bound to be problematic. It is nevertheless an important feature of organizational life and, therefore, a fruitful framework for understanding complex organizations. The article suggests that in the particular organization studied, issues of management control are expressed in various ways which reflect a chain of command, being alternatively brought into sharp focus and then blurred. It is suggested that this can be seen to represent activities which involve considerable components of what ethnomethodologists might call ‘artful practice’.